Síntese da ferrita de zinco e óxido de zinco pelo método sol gel proteico - Oliveira, Renato César de Souza (2017)
In this work, the synthesis of zinc ferrite (ZnFe2O4) and zinc oxide (ZnO) by the protein sol-gel method with pear orange albedo pectin, which can be harvested from organic waste, was carried out. The reagents used in the synthesis were the nitrate salts of iron III nonahydrate (Fe(NO3)3•9H2O) and zinc nitrate hexahydrate (Zn(NO3)2•6H2O). The nitrate mixture with pectin was subjected to a 4 hour heat treatment at temperatures of 1073 K, 1173 K, 1273 K, 1373 K, 1373 K and 1573 K. The influence of the heat treatments on the properties of the material was studied using spectroscopy techniques In infrared, X - ray diffraction and Mössbauer spectroscopy, the latter only for zinc ferrite. ZnFe2O4, hematite (Fe2O3) and ZnO phases are present in the characterization of zinc ferrite, the hematite is detected in the three techniques up to 1173 K and ceases to exist in 1273 K, the zinc ferrite phase encounters Is present in all techniques as the main phase. ZnO is identified in the infrared spectroscopy and X - ray diffraction techniques, being observed in all the samples, but with reduction of concentration as a function of the increase of the temperature, reaching its minimum in 1573 K. For presenting unexpected magnetic properties Sample of zinc ferrite produced at 1573 K was subjected to the oil loading test obtaining a result of 3.6 times the mass of the oil mass in relation to its mass. In the ZnO samples two phases are present in the infrared spectrum, the ZnO and a phase still unknown, while the X - Ray diffractogram shows all the characteristic peaks referring to the ZnO itself.